Brenner Tumor Found Incidentally in a Hysterectomised Patient: A Case Report - Güvendağ Güven, Seda; Akpınar, Funda; Bağcı, Pelin (Gynecology Obstetrics & Reproductive Medicine, 2012)
Brenner tumors are uncommon neoplasms of the ovary accounting for 1.5-2% of all ovarian neoplasms. They arise from ovarian surface epithelium or pelvic mesothelium through transitional metaplasia. In 30% cases an association with another epithelial ovarian neoplasm is observed. They are usually diagnosed incidentally in pathologic examination. This case report emphasis on the decision to perform an elective bilateral salpingo-oophorectomy (BSO) at the time of a hysterectomy for a benign condition in postmenopausal women.